Effect of polymer concentration on morphology, dielectric and optical properties in a polymer-dispersed ferroelectric liquid crystal. Issue 5 (8th April 2016) - Jayoti, Divya; Khushboo,; Malik, Praveen; Singh, Arshdeep
ABSTRACT: Photocurable polymer-dispersed ferroelectric liquid crystal were prepared by polymerisation-induced phase separation (PIPS). Morphological behaviour was analysed by polarising optical microscopy (POM) and scanning electron microscopy (SEM). FLC droplet size was found in the range of ~ 2–70 µm and decreases with an increase in polymer content. Relaxation frequency, dielectric strength and ac conductivity were evaluated as a function of polymer concentration and it was concluded that the polymer concentration has a significant effect on these parameters. The energy band gap ( ) increases with polymer concentration and was found in the range of ~ 3.3 eV at higher concentration of polymer. Graphical Abstract: